2010
DOI: 10.1080/10934529.2010.493812
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Remazol Black B dye (Azo dye) by the growingAspergillus flavus

Abstract: In the present study, an attempt was made for the removal of Remazol Black B dye (azo dye) by using Aspergillus Flavus during its growth. Biosorption of the azo dye by growing fungi was investigated in batch reactors as a function of initial concentration of dye (25-1000 mg/L), inoculum concentration (5-20%), and pH (2.5-6.5). The total biomass concentration decreased from 6.3 g/L to 1.44 g/L by increasing the dye concentration from 0 to 1000 mg/L. The dye uptake increased from 4.37 to 233 mg/g of dried biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 32 publications
1
11
0
2
Order By: Relevance
“…Semakin tinggi konsentrasi ion logam maka efisiensi penyerapan biomassa akan semakin rendah. Hal itu dikarenakan peningkatan jumlah ion logam semakin meningkat untuk dapat berikatan dengan biomassa dan kurangnya sisi kompleksitas dari biomassa untuk mengikat seluruh ion logam (Ranjusha et al, 2010).…”
Section: Penggunaan Ulang Jamur Pelapuk Putih Omphalina Sp (Reuse)unclassified
“…Semakin tinggi konsentrasi ion logam maka efisiensi penyerapan biomassa akan semakin rendah. Hal itu dikarenakan peningkatan jumlah ion logam semakin meningkat untuk dapat berikatan dengan biomassa dan kurangnya sisi kompleksitas dari biomassa untuk mengikat seluruh ion logam (Ranjusha et al, 2010).…”
Section: Penggunaan Ulang Jamur Pelapuk Putih Omphalina Sp (Reuse)unclassified
“…The dead biomass of A. niger has high ability to absorb dye wastes from textiles (Khalaf, 2008). Other studies have also revealed its biosorption of complicated dye waste from textile industries especially the azo dye (Ranjusha et al, 2010). Thus, harnessing fungal products for industrial processing of textiles in developing countries including Tanzania would improve and promote sustainable production.…”
Section: Aspergillus Species For Textile Processingmentioning
confidence: 99%
“…The nearly complete removal of dye was found at initial concentration up to 250 mg/L and at pH 4.5 which was used as working pH value for removal of dye in all the batch studies. The removal of chemical oxygen demand (COD) was found to be 90% at 100 mg/L initial concentration of dye [4]. Metal-organic frameworks (MOFs) are hybrid materials with ordered three-dimensional frameworks via strong metal-ligand bonds between metal cations and organic linkers [5].…”
Section: Introductionmentioning
confidence: 99%
“…Textural properties of ZIF-8 andFe-ZIF-8.BET : specific surface area calculated by BET model;2 Langmuir : specific surface area calculated by Langmuir model; 3 pore : pore diameter calculated by BJH model;4 …”
mentioning
confidence: 99%